PRIORITY PRINCIPLES OF ONLINE BUYING AND SELLING IN AN ISLAMIC PERSPECTIVE - Risni, Titin Widya; Hendy; Syahidah, Nila Lukmatus; Santoso, Kukuh (Universitas Muhammadiyah Bengkulu, 2025)
The research was carried out by carrying out weighted pairwise comparisons on 4 criteria, namely that there were no causes for delays in the transaction assembly, Ittihad al-majlis, the Sayyid Sabiq model, and did not contain elements of gharar-maisyir. The results of the AHP analysis can ensure that online buying and selling transactions carried out via online platforms are in accordance with Islamic principles and provide good benefits for all parties involved, thus increasing the economic of the community and strengthening the economy of the Muslim community. In the context of Islamic business, the importance of maintaining clarity and openness in transactions and maintaining time compliance is crucial. This can be the key to success in transactions and also as a form of social responsibility for Islamic business actors. Not only that, integration and balancing the interests of the parties involved in the transaction, as well as avoiding elements of uncertainty and gambling must also be considered so that transactions can run in accordance with Islamic sharia principles. Therefore, appropriate strategic steps need to be taken so that Islamic buying and selling transactions can be carried out well, in accordance with Islamic sharia principles, and provide maximum benefits for all parties involved